Profil musculaire isocinétique du genou chez des sprinteurs et des sauteurs de haut niveau - Hammami, R.; Chaouachi, A.; Ben Achour Lebib, S.; Dziri, C.; Ben Salah, F.-Z. (Science & Sports, 2011)
Purpose To study the isokinetic knee strength profile in elite sprinters and jumpers with recurrent hamstring injuries. Method A group of eight elite athletes including sprinters and jumpers with previous hamstring injuries were compared to a control group of non-injured players (n = 8). The concentric isokinetic knee flexion and extension strength was assessed at 60, 120 and 180 °/s using a Biodex® System 3 dynamometer. Results There were no significant differences for any of the isokinetic variables comparing the injured and the non-injured athletes except for the hamstring to quadriceps ratio, which is lower in the control group. No significant difference was observed between the dominant and the non-dominant leg for the two groups. Conclusion Isokinetic muscle strength testing allows to detect the existence of a strength deficit after a hamstring injury during sports practice. Additional eccentric tests may be required to identify these cases.